Evolution of an agriculture-associated disease causing Campylobacter coli clade: evidence from national surveillance data in Scotland. - Samuel K Sheppard; John F Dallas; Daniel J Wilson; Norval J C Strachan; Noel D McCarthy; Keith A Jolley; Frances M Colles; Ovidiu Rotariu; Iain D Ogden; Ken J Forbes; Martin C J Maiden (PLoS ONE)
The common zoonotic pathogen Campylobacter coli is an important cause of bacterial gastroenteritis worldwide but its evolution is incompletely understood. Using multilocus sequence type (MLST) data of 7 housekeeping genes from a national survey of Campylobacter in Scotland (2005/6), and a combined population genetic-phylogenetics approach, we investigated the evolutionary history of C. coli. Genealogical reconstruction of isolates from clinical infection, farm animals and the environment, revealed a three-clade genetic structure. The majority of farm animal, and all disease causing genotypes belonged to a single clade (clade 1) which had comparatively low synonymous sequence diversity, little deep branching genetic structure, and a higher number of shared alleles providing evidence of recent clonal decent. Calibration of the rate of molecular evolution, based on within-species genetic variation, estimated a more rapid rate of evolution than in traditional estimates. This placed the divergence of the clades at less than 2500 years ago, consistent with the introduction of an agricultural niche having had an effect upon the evolution of the C. coli clades. Attribution of clinical isolate genotypes to source, using an asymmetric island model, confirmed that strains from chicken and ruminants, and not pigs or turkeys, are the principal source of human C. coli infection. Taken together these analyses are consistent with an evolutionary scenario describing the emergence of agriculture-associated C. coli lineage that is an important human pathogen.